Effect of Plate Wettability on Dispersed-Phase Holdup in a Pulsed Disc-and-Doughnut Solvent Extraction Column. Issue 7 (10th November 2017) - Grabin, Teobaldo; Smith, Kathryn H.; Mumford, Kathryn A.; Wang, Yong; Stevens, Geoffrey W.
ABSTRACT: The effect of plate wettability on the dispersed-phase holdup in a pulsed disc-and-doughnut solvent extraction column is presented. Teflon, nylon, and stainless steel plates have been used to simulate a change in the wetting characteristics of the plate material that can occur in an operating column due to ageing or deposits accumulating on the plate. Experimental holdup data have been measured over a range of operating conditions using a 1.0 m long glass column with an internal diameter of 72.5 mm containing alternating discs and doughnuts. The liquid-liquid system studied was tri-n-octylamine (TOA)-kerosene-water with sulphuric acid as the solute. Results show that there are noticeable changes in the characteristic velocity (determined from measured holdup) and operational regimes for the different plate materials, particularly at low pulsation intensities, when operating under dispersed aqueous conditions. Experimental holdup data from this study have also been compared to correlations from literature for predicting holdup. As none of these correlations for holdup incorporate plate wettability, a new correlation for predicting holdup has been proposed that incorporates the contact angle of the plate material to allow for changes in the wettability of the plate surface. This correlation is able to predict the holdup data from this study to within 10.5% for aqueous dispersed conditions.